A new species of the leafhopper genus Matsumuratettix Metcalf (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) from Thailand - Duan, Yani; Dietrich, Christopher H.; Zhang, Yalin (Zootaxa, 2016)
Matsumura (1914) established Epitettix with the type species E. hiroglyphicus Matsumura, 1914 from Taiwan. Metcalf (1952) proposed the new name Matsumuratettix for Epitettix Matsumura, which was preoccupied by Epitettix Hancock, 1907. Dash & Viraktamath (1995) synonymised Pruthiorosius Ghauri with Matsumuratettix Metcalf. Currently, Matsumuratettix comprises a single species, M. hiroglyphicus (Matsumura, 1914). The genus is easily distinguished from other Old World Deltocephalini by the aedeagal shaft being strongly laterally compressed over the distal two-thirds and with asymmetrical distal spines. In this paper, a new species is described from Thailand and a key to distinguish the two known species is provided.